8DSS-promoted remineralization of demineralized dentin in vitro1. Issue 33 (7th September 2015) - Liang, Kunneng; Xiao, Shimeng; Shi, Wenyuan; Li, Jianshu; Yang, Xiao; Gao, Yuan; Gou, Yaping; Hao, Liying; He, Libang; Cheng, Lei; Xu, Xin; Zhou, Xuedong; et al.
<x xml:space="preserve">Abstract</x> The 8DSS peptide successfully induced nano-crystals precipitation on the collagen matrix. The completely demineralized dentin was effectively remineralized and its mechanical properties were significantly improved.